Factors Associated with Poor Sleep among Young People in Mauritius: A Survey-Based Study - Ramdhany, Yudisha Devi; Devi Goorah, Smita Sulackshana; Cheeneebash, Jayrani; Niketan Oodun, Ritwij (International Journal of Medical Students, 2022)
Background: Poor sleep quality in young people is a global concern. This study was conducted to explore sleep quality and its contributory factors in young people of Mauritius. Methods: This cross-sectional study comprised 202 participants aged between 14 to 29 years. The Pittsburgh Sleep Quality Index (PSQI), the Epworth Sleepiness Scale (ESS) and the Adolescent Sleep Hygiene Scale (ASHS) were used to measure sleep quality, daytime sleepiness, and sleep hygiene respectively. Chi-squared tests were conducted to evaluate relationships between the collected variables. Multivariate logistic regression was used to identify associated factors with poor sleep quality. Results: The mean global PSQI was 4.81 (95%CI: 4.4, 5.22). Prevalence of poor sleep quality (global PSQI score > 5) was 30.7%. The male gender reported better sleep (p=0.008). Sleep quality was significantly associated with longer sleep duration (p<0.0001), pre-bedtime relaxing activities (p=0.01), and daytime physical exercise (p=0.001). In contrast, alcohol consumption after 18:00 (p<0.0001), tobacco smoking after 18:00 (p<0.0001), pre-bedtime awakening activities (p=0.001), and poor sleep environment (p<0.0001) negatively influenced sleep quality. Multivariate logistic regression confirmed that female gender and sleep environment factors were associated with higher likelihood of poor sleep quality, while participants with longer duration of sleep (>7 hours), cognitive/emotional and sleep stability factors were found to be less likely to have poor sleep quality. Conclusion: This study showed that the prevalence of poor sleep in young people in Mauritius was 30.7%. Female gender and sleep environment factors were main contributory factors. These initial results can guide further research on sleep quality